Silicon carbide (SiC) insulated gate bipolar transistors (IGBTs) for high voltage applications - Almpanis, Ioannis (2024)
The significant interest that SiC has attracted over the last decades, coupled with the ease of voltage control and low conduction losses of the IGBTs, have led to their development and sample fabrication. Although these devices demonstrated the advantages that SiC IGBTs can bring in High Voltage power applications, their characteristics are not yet fully understood and their structure is far from optimised. This thesis addresses specific gaps in knowledge around accurate device modelling and optimisation of SiC IGBTs considering efficiency and ruggedness.